Ethiopia hygiene practice during complementary feeding and associated factors; systematic review and meta-analysis - Getnet Alemu Andargie; Kedir Seid; Gebeyehu Lakew; Amlaku Nigusie Yirsaw; Alemshet Yirga Berhie; Asnake Gashaw Belayneh; Solomon Ketema Bogale; Eyob Ketema Bogale; Eyob Getachew (BMC Pediatrics)
Abstract Background Complementary feeding is crucial for infant growth, but poor hygiene during this period increases the risk of malnutrition and illness. In Ethiopia, national data on hygiene practices during complementary feeding, particularly among mothers of children aged 6–24 months, is limited. This study aims to synthesize existing data through a systematic review and meta-analysis to evaluate the status of hygiene practices and identify key influencing factors, informing public health strategies to improve child health outcomes. Methods The systematic review methods were defined following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A search strategy was implemented using electronic databases (Medline, Global Health, Google Scholar, Web of Science, Embase, CINAHL, and Psyc INFO) as well as grey literature. The Joanna Briggs Institute (JBI) critical appraisal checklist was used to assess the quality of the studies. The meta-analysis was conducted using STATA 17 software to compute pooled prevalence and odds ratios (OR) for the determinant factors, with a 95% confidence interval (CI). Results The systematic review and meta-analysis included six studies with 2,565 mothers. The overall pooled prevalence of hygienic practices during complementary feeding was 42% (95% CI: 35%–48%). Subgroup analysis showed a prevalence of 41% in southern Ethiopia and 39% in northern Ethiopia. Significant factors associated with better hygiene practices included having hand washing facilities near toilets (AOR: 4.6, 95% CI: 1.04–8.31, p = 0.01) and a positive attitude towards hygiene (AOR: 2.7, 95% CI: 1.07–4.69, p < 0.05). Conclusions This systematic review and meta-analysis found a low proportion of hygienic practices during complementary feeding in Ethiopia, with maternal attitude and access to hand washing facilities identified as key predictors. Training and counseling for mothers on safe food processing are recommended, along with further research on community interventions and the impact of socio-economic factors on hygiene practices.